Kualitas Laporan Keuangan Pemerintah Daerah (Studi Kasus pada BPKAD Kabupaten Manokwari) - Maspaitella, Marcus; Mokodompit, Mona Permatasari (Jurnal Profita: Komunikasi Ilmiah Akuntansi dan Perpajakan, 2022)
Local government financial reports are used in determining decisions that can lead to better governance. Therefore, the government is required to be able to manage regional finances in a transparent and accountable manner in order to produce quality financial reports. The purpose of this study is to analyze the factors that influence the quality of local government financial reports at the Regional Financial and Asset Management Agency (BPKAD) of Manokwari Regency. The factors analyzed include human resource competence, regional financial accounting information systems, use of information technology and government internal control systems. This research is a quantitative research. The research data collected by giving questionnaires to all employees who work in the BPKAD office of Manokwari regency. The data was then analyzed using multiple linear regression analysis. The results show that out of the four factors analyzed, only the government internal control system factor have influence on the quality of local government financial reports at BPKAD Manokwari regency. Meanwhile, human resource competence, regional financial accounting information systems and the use of information technology have no influence on the quality of local government financial reports at BPKAD Manokwari regency.